„Ultimii” critici, între geometrie și finite - Raluca Dună (Revista de Istorie și Teorie Literară)
This article is focused on major ideas of a book discussing the destiny of European XXth century criticism. „Geometry and Refinement”, by Mircea Martin follows the fundamental tensions of French criticism, mainly the intellectual versus the sensitive trend, the balance between the quest for the particular and individual element versus the opposite search for the generic form, a system of oppositions that may be resumed into one formula: ‟esprit de finesse” versus „esprit de géometrie”. Mircea Martin demonstrates that the Pascalian duality is in fact contradicted by the subtle paradoxes of those great, last critics who reinvented literature in their effort to render the dialogue with themselves into a relevant, transparent dialogue with the otherness of literature.